Bridging The Digital Divide: The Effectiveness Of Gadget Provision Programs And Digital Literacy Training For Marginalized Students In Improving Access And Learning Outcomes (A Longitudinal Study) - Tri Handayani; Wajnah; Andi Hidayati; Musa Hefer Smas; Bernardus Agus Rukiyanto (Academy of Education Journal, 2026)
The digital divide remains a significant barrier to equitable educational access in developing nations, particularly affecting marginalized students in underserved regions. This longitudinal qualitative study examines the effectiveness of a device provision and digital literacy training program implemented across three schools in rural Indonesia over an 18-month period. Utilizing semi-structured interviews with 45 students and 18 educators, combined with classroom observations and document analysis, this research employs thematic analysis to identify how coordinated hardware provision and pedagogical training influence student learning access and academic outcomes. Key findings reveal that device provision alone demonstrates limited efficacy; however, when coupled with structured digital literacy training and teacher professional development, significant improvements emerge in student engagement (73% increase), digital skill competencies (average gain of 2.4 proficiency levels), and learning outcomes (28% improvement in academic performance). The study identifies critical success factors including sustained teacher training, contextual curriculum adaptation, and family literacy support. Findings suggest that addressing the digital divide requires multifaceted approaches beyond infrastructure investment, emphasizing the need for integrated educational interventions that consider local socioeconomic contexts and teacher capacity. This research contributes to evidence-based policy recommendations for equitable technology integration in marginalized educational settings.